2013
DOI: 10.1093/tropej/fmt017
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial Transmission of Hepatitis C Infection in Egyptian Multitransfused Thalassemia Patients

Abstract: Our results support the role of intrafamilial transmission in the spread of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…In the present study, more than 37% of patients were positive for anti-HCV. These results can be compared with previously conducted studies from other regions of Egypt, such as anti-HCV in one Egyptian report of about 34% [ 7 ], and in another study of about 24% [ 8 ]. Moreover, in other countries, anti-HCV-positive cases were about 40.5% in Jordan [ 21 ], 30% in India [ 22 ], and 35% in Pakistan [ 23 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the present study, more than 37% of patients were positive for anti-HCV. These results can be compared with previously conducted studies from other regions of Egypt, such as anti-HCV in one Egyptian report of about 34% [ 7 ], and in another study of about 24% [ 8 ]. Moreover, in other countries, anti-HCV-positive cases were about 40.5% in Jordan [ 21 ], 30% in India [ 22 ], and 35% in Pakistan [ 23 ].…”
Section: Discussionmentioning
confidence: 62%
“…In Egypt the lack of a central surveillance system for disease epidemiology is a major obstacle regarding the assessment of the current situation of infectious diseases, including TTIs, and, therefore, regional and periodic studies are the only option to monitor recent developments. There are only a few studies about TTIs in thalassemic children in Egypt [ 3 , 7 9 ]. To our knowledge, no study has described the situation of TTIs in thalassemic children in Upper Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals were predominantly infected with genotype 4 regardless of population type. Genotype 4 was found among blood donors 114 117 , pregnant women 118 , village residents 76 , outpatients 119 , Egyptian expatriate general populations 75 , 120 , thalassemia patients 121 , hemodialysis patients 122 , healthcare workers 123 , 124 , children of HCV infected mothers 60 , household contacts of HCV infected individuals 52 , hospitalized populations 125 , diabetic patients 126 , hepatocellular carcinoma patients 127 , chronic liver disease patients 83 , 125 , 128 , 129 , acute viral hepatitis patients 130 132 , special clinical populations 133 139 , and mixed populations 140 142 . Studies also identified a wide array of subtypes for genotype 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the study of Said et al . [ 35 ] in Egypt revealed that 19.2% of family members of anti-HCV + thalassemia patients are also seropositive. Therefore, the transmission of HCV might be through saliva and as a result is dependent on the lifestyle of the patient and his/her family.…”
Section: Discussionmentioning
confidence: 99%